Migrating grass awn within the intraconal part of the retrobulbar space in a dog. (2nd March 2021) - Collard, C.; Garnier, P.; Gory, G.; Cabon, Q.
Abstract : A 1.5‐year‐old MC Cardigan Welsh Corgi was presented for a right oral fistula associated with left tonsil enlargement that responded to medical treatment. A first computed tomography scan was performed and showed no signs of a foreign body. Medical treatment was continued for 2 additional weeks and the dog was free of clinical signs for 3 months. The dog was presented again for a 3‐day history of anorexia and marked pain when opening the jaw. The repeat computed tomography scan revealed a migrating foreign body near the optic canal of the right eye, and surgical exploration confirmed that it was trapped within the intraconal part of the retrobulbar space, abutting the optic nerve. The foreign body was surgically removed through an osteotomy of the zygomatic bone. The dog fully recovered with no vision loss. Based on the literature search, this is the first published report describing a migrating grass awn located in the intraconal part of the retrobulbar space, abutting the optic nerve.